NF-κB regulates MICA gene transcription in endothelial cell through a genetically inhibitable control site. - Lin, D; Lavender, H; Soilleux, E; O'Callaghan, C (2012)
Endothelial cells form a barrier between blood and the underlying vessel wall, which characteristically demonstrates inflammatory damage in atherosclerotic disease. MICA is a highly polymorphic ligand for the activating immune receptor NKG2D and can be expressed on endothelial cells. We hypothesized that damaged vessel walls, such as those involved in atherosclerosis, might express MICA, which could contribute to the vascular immunopathology. Immune activation resulting from MICA expression could play a significant role in the development of vascular damage. We have demonstrated that TNFα up-regulates MICA on human endothelial cells. The up-regulation is mediated by NF-κB, and we have defined the regulatory control site responsible for this at -130 bp upstream of the MICA transcription start site. This site overlaps with a heat shock response element and integrates input from the two pathways. We have shown that in atherosclerotic lesions there is expression of MICA on endothelial cells. Using lentivirus-mediated gene delivery in primary human endothelial cells, we were able to inhibit the MICA response to TNFα with a truncated HSF1 that lacked a transactivation domain. This highlights the potential for transcription-based therapeutic approaches in atherosclerotic vascular disease to reduce immune-mediated endothelial and vessel wall damage.